Respuesta :

Answer:

Step-by-step explanation:

a). By applying tangent rule in the triangle,

   tanθ = [tex]\frac{\text{Opposite side}}{\text{Adjacent side}}=\frac{3}{4}[/tex]

   θ = [tex]\text{tan}^{-1}(\frac{3}{4})[/tex]

   θ = 36.87°

   Therefore, θ < 45°

b). By using cosine rule in this triangle,

   cosθ = [tex]\frac{\text{Adjacent side}}{\text{Hypotenuse}}=\frac{18}{18\sqrt{2}}[/tex]

   cosθ = [tex]\frac{1}{\sqrt{2}}[/tex]

    θ = 45°

c). By using tangent rule,

  tanθ = [tex]\frac{\text{Opposite side}}{\text{Adjacent side}}=\frac{8}{2}[/tex]

  θ = [tex]\text{tan}^{-1}(4)[/tex]

  θ = 75.96°

  θ > 45°